Fate and Consolation in the Late Rousseau - Yamashita, Masano (Sens public, 2019)
In his last writings Rousseau attempts to understand the events of his life as the products of fate. This essay analyzes the valences of fate in relation to concepts such as fatality and Providence. Rousseau engages with a diverse and at times contradictory corpus of ideas (stoicism, epicureanism, materialism, Protestantism) and an eclectic set of anecdotes (visit to the Invalides, personal memories of times spent with Madame de Warens) that aim to console him in his misfortunes. Only philosophizing and consolations allow Rousseau to ultimately free himself from the influence of his adversaries.